Estudio de factibilidad para el desarrollo de un sistema de control del personal de limpieza e insumos para la Asociación Serviplus de la ciudad de Babahoyo. - Ramírez Guardado, Jefferson Javier (2022)
Technology has now become a fundamental support of Ecuadorian society, the novelty in technological tools is to provide simple resources in our daily tasks. For companies, technology is essential because of the amount of information that is handled. The control systems take more presence in the business sector, because they allow management of the information in an effective way, thus controlling all the computer resources, perfecting the processes that are previously performed manually. With the development of a control system for cleaning personnel and supplies for the company serviplus in the city of Babahoyo, it will be possible to solve several problems that can be observed with the naked eye, relying on technology to obtain better results. The control system for cleaning and supplies personnel for the company serviplus in the city of Babahoyo has been developed in an open source programming language, scalable function modules and a simple user interface.